Optimizing BSI Mobile Banking Services to Increase Satisfaction with Transaction Services for IAIN Madura Sharia Banking Study Program Students With a SWOT Analysis Approach - Lailiyah, Istiq; Umam, Khotibul; Fahrurrozi, Fahrurrozi; Sakinah, Sakinah; Hakim, Lukmanul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This research is presented to contribute to what business strategies Bank Syariah Indonesia can optimize in optimizing BSI mobile services for transaction satisfaction using a SWOT analysis approach. Data analysis was carried out by exploring data through observation, interviews and documentation, which was followed by a data reduction process, testing data validity and drawing conclusions. Based on the results of the SWOT analysis, researchers found that BSI mobile banking services are currently at coordinates 0.70; 0.51, where these coordinates are in quadrant 1, namely an aggressive strategy. This strategy shows the situation that BSI bank can optimize BSI mobile banking services in increasing satisfaction by using all their strengths to take advantage of existing opportunities. One of these strategies can be in the form of (1) Improving the quality of products and service features (2) Maintaining the satisfaction of existing customers by improving the quality of transactions that are safe, precise and fast, (3) Increasing the security protection of customer data, (4) Evaluating feedback from past and current customers in designing future market share, (5) Strengthening promotional tools in introducing the benefits of BSI Mobile Banking service features, and (6) Reaching potential new customers in expanding market expansion .